HEALTH EDUCATION ABOUT BULLYING AT JUNIOR HIGH SCHOOL 7 SUNGAI RAYA IN PONTIANAK - Lestari Makmuriana (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2022)
The phenomenon of bullying is spreading more and more among teenagers, especially in schools and cyberspace. The tendency to view bullying as just part of a joke causes the problem to be underestimated and not taken seriously. In fact, this action is very dangerous, especially for psychological victims, which often causes someone to become depressed, feel inferior and even encourage someone to commit suicide. Therefore, awareness-raising through outreach activities related to bullying needs to be carried out with the aim of providing knowledge regarding bullying acts and being able to prevent bullying from occurring in their environment. The approach method used is through counseling the impact of bullying in schools. The counseling was carried out by Junior High School 7 Sungai Raya with 40 participants. The results showed that the participants were active in giving questions and opinions about bullying in schools. 98% of participants seemed enthusiastic in obtaining information about bullying. 100% of participants seemed satisfied with the results of the discussion about. Participants understand the actions of bullying and are an effort to minimize bullying cases in the school environment.